2010
DOI: 10.3920/wmj2009.1179
|View full text |Cite
|
Sign up to set email alerts
|

Real-time PCR detection of Fusarium species in Swedish oats and correlation to T-2 and HT-2 toxin content

Abstract: Contamination of Fusarium moulds and subsequent production of mycotoxins is a common problem in cereals grown in Northern Europe. Oats is the third most important cereal crop in Sweden and is commonly contaminated by Fusarium. To date there are no published reports on the distribution of trichothecene-producing Fusaria in Swedish oats and correlation to T-2 and HT-2, the two most dominant toxins. Identification of Fusarium species by traditional methods requires specific skill and experience and quantification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…This is in accordance to other studies (Bernhoft et al, 2010;Edwards, 2009;Fredlund et al, 2010), and may indicate that the HT-2 and T-2 producers have different environmental requirements and/or epidemiology than the DON producers (Edwards, 2009;Xu et al, 2014). Based on the inverse relationship detected between HT-2 and DON in UK oats, Edwards (2009) suggested a mutual exclusion between DON and HT-2 producers.…”
Section: Fusarium Langsethiae and Associated Mycotoxinssupporting
confidence: 71%
See 2 more Smart Citations
“…This is in accordance to other studies (Bernhoft et al, 2010;Edwards, 2009;Fredlund et al, 2010), and may indicate that the HT-2 and T-2 producers have different environmental requirements and/or epidemiology than the DON producers (Edwards, 2009;Xu et al, 2014). Based on the inverse relationship detected between HT-2 and DON in UK oats, Edwards (2009) suggested a mutual exclusion between DON and HT-2 producers.…”
Section: Fusarium Langsethiae and Associated Mycotoxinssupporting
confidence: 71%
“…A higher occurrence of F. langsethiae in Norwegian oats compared to spring wheat was also documented in the period 2002(Bernhoft et al, 2010. Furthermore, positive associations between HT-2 + T-2 and F. langsethiae, as detected in our study, are reported in several studies of oats from Northern Europe (Bernhoft et al, 2010;Edwards et al, 2012;Fredlund et al, 2010Fredlund et al, , 2013. Despite the high association detected between HT-2 + T-2 content and F. langsethiae DNA in oats in our study, the level of F. langsethiae could not account for more than 51% of the total variation in HT-2 + T-2.…”
Section: Fusarium Langsethiae and Associated Mycotoxinssupporting
confidence: 65%
See 1 more Smart Citation
“…Generally, a good correspondence was noted between DNA of F. langsethiae and the T-2/HT-2 toxins detected in grain samples [43,44,45,46,47]. …”
Section: Discussionmentioning
confidence: 99%
“…langsethiae is frequently detected in grains when using species-specific primers; quantitative PCR offers an efficient estimation of the biomass of individual species. Generally, a good correspondence was noted between DNA of F. langsethiae and the T-2/HT-2 toxins detected in grain samples [43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%